2020
DOI: 10.2174/1389202921999200604123914
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA Sequencing: In-depth Decoding of Heart Biology and Cardiovascular Diseases

Abstract: Background: The cardiac system is a combination of a complex structure, various cells, and versatile specified functions and sophisticated regulatory mechanisms. Moreover, cardiac diseases that encompass a wide range of endogenous conditions, remain a serious health burden worldwide. Recent genome-wide profiling techniques have taken the lead in uncovering a new realm of cell types and molecular programs driving physiological and pathological processes in various organs and diseases. In particular, the emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 117 publications
0
6
0
Order By: Relevance
“…Recently, several studies have identified a method to activate HOPX, a key development regulator of CMs, suggesting that stimulating HOPX might facilitate the maturation of hiPSC-CMs in-vitro. 20) 30) Furthermore, the data from scRNA-seq and bulk RNA suggested that NR2F2 and HEY2 promoted the earlier atrial-like and ventricular-like properties in hiPSC-CMs respectively. 20) 31) Although there is on-going research on identifying the regulators of CM maturation and factors that induce differentiation into specific CM subtypes, the result from in-vitro studies might not fully reflect the in-vivo human development.…”
Section: Single Cell Rna Sequencing In Heart Developmentmentioning
confidence: 98%
See 2 more Smart Citations
“…Recently, several studies have identified a method to activate HOPX, a key development regulator of CMs, suggesting that stimulating HOPX might facilitate the maturation of hiPSC-CMs in-vitro. 20) 30) Furthermore, the data from scRNA-seq and bulk RNA suggested that NR2F2 and HEY2 promoted the earlier atrial-like and ventricular-like properties in hiPSC-CMs respectively. 20) 31) Although there is on-going research on identifying the regulators of CM maturation and factors that induce differentiation into specific CM subtypes, the result from in-vitro studies might not fully reflect the in-vivo human development.…”
Section: Single Cell Rna Sequencing In Heart Developmentmentioning
confidence: 98%
“… 20) 30) Furthermore, the data from scRNA-seq and bulk RNA suggested that NR2F2 and HEY2 promoted the earlier atrial-like and ventricular-like properties in hiPSC-CMs respectively. 20) 31) Although there is on-going research on identifying the regulators of CM maturation and factors that induce differentiation into specific CM subtypes, the result from in-vitro studies might not fully reflect the in-vivo human development. However, it will still be useful to model a normal and abnormal heart tissues for the subsequence endeavor in elucidating the pathogenesis of congenital heart diseases.…”
Section: Single Cell Rna Sequencing In Heart Developmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The pathogenesis related to the cardiovascular system has not been fully elucidated due to the diverse cellular interactions and complex regulatory mechanisms. Although there has been great progress in the diagnosis and treatment of cardiovascular disease owing to the development of anatomy, genomics, and other disciplines and the development of inspection technology ( 2 ), understanding the cellular heterogeneity and gene interactions in cardiac tissue development and cardiac cell differentiation trajectories and in disease states requires further research. The limitations of action hinder the in-depth study of the pathogenesis and the effectiveness of diagnosis and treatment plans.…”
Section: Introductionmentioning
confidence: 99%
“…The review entitled Single-cell RNA Sequencing: In-depth Decoding of Heart Biology and Cardiovascular Diseases by Dr. Chen [ 4 ] reviewed recent advances in single cell studies of cardiovascular system and summarized new insights provided by scRNA-seq in heart developmental sciences, stem-cell researches as well as normal or disease-related mechanisms.…”
mentioning
confidence: 99%